Transformasi Digital, Kapabilitas Strategis, dan Kinerja Layanan Administrasi Perguruan Tinggi: Kajian Literatur - Victorio Fernando Nahumay; Deflin Tresye Nanulaitta; Cynthia Imelda Tjokro; Simson Melmambessy (P3M Politeknik Negeri Ambon, 2026)
Digital transformation has become a strategic demand for higher education institutions because it is closely related to the improvement of efficiency, accuracy, transparency, and the quality of administrative services. However, technology adoption does not automatically improve service performance without the support of organizational strategic capabilities. This study aims to analyze the role of digital transformation and organizational strategic capabilities in improving administrative service performance in higher education institutions. This research employed a structured literature review by examining relevant scientific publications on digital transformation, strategic capabilities, digital leadership, human resource readiness, and service performance. The literature was analyzed thematically to identify conceptual patterns and relationships among variables. The findings show that digital transformation involves not only the use of technology, but also changes in work processes, governance, organizational culture, and decision-making. Organizational strategic capabilities act as a key link between digital transformation and improved administrative service performance. Digital leadership, human resource competence, innovation culture, and organizational adaptability are the major factors that produce faster, more accurate, transparent, and responsive services. The study concludes that the success of digital transformation in higher education depends on strengthening organizational strategic capabilities so that technology can generate real value in administrative services. Keywords: digital transformation; organizational strategic capabilities; administrative service performance; higher education institutions